(untitled) (Economics and region, 2023)
Globalization processes are developing more and more actively in world society over the years. World associations of countries are formed, replenished and developed, world corporations are formed, knowledge is exchanged and associations to solve global problems take place. Ukraine, as a democratic, independent, sovereign state, is moving towards the European Union, but in the context of European integration, the country needs to carry out a number of reforms in order to meet European standards. Thus, in 2015, a number of reforms in various spheres of activity were approved in Ukraine. One significant reform was the reform of decentralization, but it continues to be implemented today. When developing the plan for the implementation of the decentralization reform, it was not foreseen in advance that the country would face a low number of challenges and threats. First it’s a global pandemic in 2020, then a war on February 24, 2022. Armed aggression against Ukraine changed the priority directions of the country’s development as a whole. Today, it is of primary importance to work for victory, defense capability and support of the population. Of course, such nationwide threats were not foreseen in the decentralization reform and territorial communities need to change the tactics of further political development. The article describes the process of formation of the decentralization reform, its political and economic consequences. Planning and implementation of the strategy for the development of terminal communities, as well as the formation of regional economic policy under martial law. Consider in more detail the priority of further development and budgeting of communities. It was found that the martial law had a significant impact on the beginning of the full-scale invasion, where the decentralization policy lost its delegated powers and the centralization of financial flows became a priority. Of course, every socio-economic challenge has its own consequences, but with the support of Western partners, which is effective diplomacy, Ukraine managed to stabilize the national economy. Expenditures of the local budget in the conditions of the war predictably changed their directions to public safety. This item of expenditure during the war increased 10 times, and the direction of strategic planning changed mostly to the construction of shelters, rehabilitation of servicemen and victims of the war. At the same time, with the help of state and European support, spending on the development of education and digitization remains a priority. Thus, Ukraine will still have to make and adjust a lot of decisions regarding further effective policy, but it has weathered the complex economic tension and continues to develop as a sovereign, democratic, independent European state.